2016
DOI: 10.1016/j.physletb.2016.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the X (5568)

Abstract: A variety of options for interpreting the DØ state, X(5568), are examined. We find that threshold, cusp, molecular, and tetraquark models are all unfavoured. Several experimental tests for unravelling the nature of the signal are suggested.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 67 publications
4
70
0
Order By: Relevance
“…Also the authors of Ref. [23] deduced a lower limit for the masses of a possible (bsud) tetraquark state: 6019 (6107) MeV. Complementary to Ref.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Also the authors of Ref. [23] deduced a lower limit for the masses of a possible (bsud) tetraquark state: 6019 (6107) MeV. Complementary to Ref.…”
Section: Introductionmentioning
confidence: 72%
“…In Ref. [23] a few options for the interpretation of the X(5586) state have been checked. It was concluded that threshold, cusp, molecular, and tetraquark approaches for the explanation of the X(5586) state are all disfavored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, right after the observation by D0, the possible existence of this state was challenged on theoretical grounds; see Refs. [67][68][69]. The reason of its appearance in the D0 and absence in LHCb and CMS experiments is discussed in Ref.…”
Section: Rescattering Amplitudementioning
confidence: 99%
“…The authors of Ref. [32] regard that neither a molecular state nor a tetraquark can explain the data, so they consider that B s π is produced in an electroweak decay where an extra hadron is also created, but evades detection.…”
Section: Introductionmentioning
confidence: 99%